Comparative Effects of Trichoderma and EM4 in Aerobic–Anaerobic Tiered-Bucket Production on Liquid Organic Fertilizer and Compost Quality - Ansyori, Ansyori; Lamdo, Herfandi; Anissa, Nabillah (Universitas Panji Sakti, 2025)
Organic waste is an abundant resource but remains underutilized as a safe and nutrient-rich organic fertilizer. This study aims to evaluate the effectiveness of Trichoderma as an alternative bioactivator to EM4 in improving the quality of liquid organic fertilizer (LOF) and compost through tiered bucket systems under aerobic (A2) and anaerobic (A1) conditions. A randomized complete block design was used with five Trichoderma doses (0; 15; 20; 25; 30 mL.L⁻¹) and EM4 (30 mL.L⁻¹) as a comparison. The liquid and solid fractions were analyzed for C, N, C/N ratio, P₂O₅, K₂O, and heavy metals (Pb, Cd, Cu) using standard methods. The data were analyzed through ANOVA and orthogonal contrast tests. Results showed that the aerobic system consistently reduced the C/N ratio, producing more mature and stable products, while the anaerobic system tended to retain higher C-organic content. These differences were statistically significant as the aerobic condition (A2) decreased the C/N ratio by 4.74 or 40.93% in liquid organic fertilizer and by 3.62 or 19.52% in compost compared to the anaerobic condition (A1), while total P₂O₅ in liquid organic fertilizer increased by about 14.81% under A2. Medium–high doses of Trichoderma (25–30 mL L⁻¹) in the aerobic system yielded the best quality in terms of maturity, whereas EM4 generally resulted in higher macro-nutrient contents (N, P₂O₅, K₂O). All heavy metal levels were far below the SNI/Ministry of Agriculture thresholds, indicating product safety. Practically, the A2–T3/T4 combination is recommended to produce mature, stable, and safe organic fertilizer, while co-inoculation strategies may be pursued to enhance nutrient content. This study confirms that Trichoderma primarily accelerates humification and stabilizes organic matter, offering a practical, low-cost option for household/community organic waste management within a circular-economy framework; accordingly, the aerobic bucket system with medium–high Trichoderma doses (A2–T3/T4) is recommended to achieve mature, stable LOF–compost. However, the findings are lab-scale and substrate-specific.